2013
DOI: 10.1007/s13280-013-0465-8
|View full text |Cite
|
Sign up to set email alerts
|

Intertidal Zone Management in the Western Indian Ocean: Assessing Current Status and Future Possibilities Using Expert Opinions

Abstract: This expert opinion study examined the current status of the intertidal zone in the Western Indian Ocean (WIO) and ranked and discussed future management approaches. Information was gathered from scientists, practitioners, and managers active in the WIO region through a questionnaire and a workshop. The experts stated that the productive intertidal environment is highly valuable for reasons such as recreation, erosion protection, and provision of edible invertebrates and fish. Several anthropogenic pressures w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 37 publications
0
27
0
Order By: Relevance
“…Seagrasses are marine flowering plants, which form extensive meadows in shallow coastal waters on all continents except Antarctica [ 1 ], [ 2 ] ( Fig 1 ). The intertidal to shallow subtidal location of most seagrasses allows relatively easy access and multiple uses as well as exposing seagrass ecosystems to both terrestrial and marine based threats [ 3 ], [ 4 ], [ 5 ]. The many threats to seagrass are causing it to rapidly disappear globally [ 3 ], [ 5 ], [ 6 ], [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Seagrasses are marine flowering plants, which form extensive meadows in shallow coastal waters on all continents except Antarctica [ 1 ], [ 2 ] ( Fig 1 ). The intertidal to shallow subtidal location of most seagrasses allows relatively easy access and multiple uses as well as exposing seagrass ecosystems to both terrestrial and marine based threats [ 3 ], [ 4 ], [ 5 ]. The many threats to seagrass are causing it to rapidly disappear globally [ 3 ], [ 5 ], [ 6 ], [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a PCoA plot showed that no significant difference in fungal communities was detected among sediments collected from tourism, dock, aquaculture and river mouth areas, which are subjected to distinct anthropogenic influences (Nordlund et al, 2014; Whitfield and Pattrick, 2015). Nutritional conditions, temperature, pH, salinity, and other characteristics of marine sediment have been found to have a strong effect on the composition of the fungal community (Jones, 2000; Guo et al, 2015; Li et al, 2016; Tisthammer et al, 2016; etc.).…”
Section: Discussionmentioning
confidence: 95%
“…These glass tubes filled with sediment were transported to the laboratory and immediately stored at -80°C until total DNA extraction was performed. For analysis of the distribution patterns of fungal communities across different habitat types, the sampled sites were designated as one of five habitat types, namely the area of aquaculture, dock, plant (where covered with mangroves and reeds), river mouth or tourism, on the basis of the main function of a specific site (Nordlund et al, 2014; Whitfield and Pattrick, 2015). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As stated by Nordlund et al . (), however, the entire WIO coastal zone is understudied whereby near‐shore sampling, as described by Leis () and Mwaluma et al . (), could provide baseline data.…”
Section: Discussionmentioning
confidence: 99%